Ultrastructural and immunocytochemical evidence of a colonial nervous system in hydroids - Kosevich, Igor A. (Frontiers in Neural Circuits, 2023)
Background As the sister group to all Bilateria, representatives of the phylum Cnidaria (sea anemones, corals, jellyfishes, and hydroids) possess a recognizable and well-developed nervous system and have attracted considerable attention over the years from neurobiologists and evo-devo researchers. Despite a long history of nervous system investigation in Cnidaria, most studies have been performed on unitary organisms. However, the majority of cnidarians are colonial (modular) organisms with unique and specific features of development and function. Nevertheless, data on the nervous system in colonial cnidarians are scarce. Within hydrozoans (Hydrozoa and Cnidaria), a structurally "simple" nervous system has been described for Hydra and zooids of several colonial species. A more complex organization of the nervous system, closely related to the animals' motile mode of life, has been shown for the medusa stage and a few siphonophores. Direct evidence of a colonial nervous system interconnecting zooids of a hydrozoan colony has been obtained only for two species, while it has been stated that in other studied species, the coenosarc lacks nerves. Methods In the present study, the presence of a nervous system in the coenosarc of three species of colonial hydroids - the athecate Clava multicornis, and thecate Dynamena pumila and Obelia longissima - was studied based on immunocytochemical and ultrastructural investigations. Results Confocal scanning laser microscopy revealed a loose system composed of delicate, mostly bipolar, neurons visualized using a combination of anti-tyrosinated and anti-acetylated a-tubulin antibodies, as well as anti-RF-amide antibodies. Only ganglion nerve cells were observed. The neurites were found in the growing stolon tips close to the tip apex. Ultrastructural data confirmed the presence of neurons in the coenosarc epidermis of all the studied species. In the coenosarc, the neurons and their processes were found to settle on the mesoglea, and the muscle processes were found to overlay the nerve cells. Some of the neurites were found to run within the mesoglea. Discussion Based on the findings, the possible role of the colonial nervous system in sessile hydroids is discussed.